The Role of Illness-Related Beliefs in Depressive, Anxiety, and Anger Symptoms: An On-line Survey in Women With Hypothyroidism - Pankowski, Daniel; Wytrychiewicz-Pankowska, Kinga; Janowski, Konrad; Pisula, Ewa; Walicka, Magdalena (Frontiers in Psychiatry, 2021)
Hypothyroidism may affect 3–8.5% of the population and is a growing global health problem. Objective: The aim of the current study was to assess the relationships between cognitive representations of this illness and the severity of symptoms of depression, anxiety, and anger in women who suffer from hypothyroidism. Methods: The study used a cross-sectional design with on-line recruitment and measurements. A total of 354 women took part in the study and completed the following questionnaires: a 5-point self-rating scale that measures the three major symptoms of hypothyroidism, the Illness-Related Beliefs Questionnaire, the Hospital Anxiety and Depression Scale – Modified (HADS-M), and a clinical and sociodemographic data questionnaire. Results: The study found a relationship between the severity of emotional distress symptoms and illness-related beliefs. These beliefs were correlated with depressive symptoms, anxiety, and anger regardless of age, education, hormone levels or time since the diagnosis. In addition, the results of regression analyses, both hierarchical and stepwise, indicated that beliefs about the disease explained relatively high levels of the outcome variables (about 30% of the variance of depressive and anxiety symptoms and 16% of anger) as measured by HADS-M. Conclusions: psychological factors seem to play an important role in the development of symptoms of depression, anxiety, and anger in patients with hypothyroidism. Psychosocial interventions targeting personal beliefs about the nature of the disease and its social aspects may be an effective way to reduce emotional distress symptoms.